A real opportunity to modify cardiovascular risk through primary care and prevention: A pilot study - Lontano, Alberto; Marziali, Eleonora; Galletti, Caterina; Mazza, Eduardo; Gambioli, Stefano; Galasso, Valerio; Mingarelli, Alessandro; D'Ambrosio, Floriana; Tamburrano, Andrea; Paolini, Massimo; Bande, Antonio; Damiani, Gianfranco; et al. (Frontiers in Public Health, 2023)
Cardiovascular diseases represent a major threat to health and primary prevention outstands as the most effective instrument to face this issue, addressing multiple risk factors at a time and influencing behavioral patterns. Community nurses have been involved in many interdisciplinary prevention activities, resulting in an effective control of cardiovascular risk factors. We conducted a pilot study aiming at describing the impact on cardiovascular risk profile of an 18-month interdisciplinary intervention on lifestyle habits. From September 2018 to May 2020 four General Practitioners (GPs) working in the Roman neighborhood of Torresina recruited patients having a cardiovascular risk score (CRS) equal to or higher than 3% and lower than 20%; those patients were included in a nutritional, physical and psychological counselling program. Assessments of patients’ health status were led at baseline, 6, 12 and 18 months by a nutritionist, a physiotherapist, a psychologist, their GP and a community nurse. The CRS was estimated at every examination, based on Italian Progetto Cuore algorithm. 76 patients were included (mean age of 54.6 years; 33 males and 43 females). Mean CRS showed a significant reduction between baseline and 12 months (from 4.9 to 3.8); Both total cholesterol and systolic blood pressure significantly decreased at 6 months of follow up (respectively, from 211.1 to 192 and from 133.1 to 123.1). Nonetheless, the reduction was later maintained only for systolic blood pressure. However, during the last six months of the intervention, the COVID-19 pandemic broke out, so it is not possible to know how much the results achieved at 18 months were influenced by the restrictive measures introduced by the Italian government. When stratifying according to the presence of hypertension/diabetes and physical activity, no differences in the CRS could be highlighted between the two groups. Our pilot study proved that an interdisciplinary counselling intervention program can improve cardiovascular risk profile and could be further spread to people that, according to their CRS, would benefit more of changes in lifestyles.